Methane biohydroxylation into methanol by Methylosinus trichosporium OB3b: possible limitations and formate use during reaction - Baldo, Héloïse; Ruiz-Valencia, Azariel; Cornette de Saint Cyr, Louis; Ramadier, Guillaume; Petit, Eddy; Belleville, Marie-Pierre; Sanchez-Marcano, José; Soussan, Laurence (Frontiers in Bioengineering and Biotechnology, 2024)
Methane (CH4) hydroxylation into methanol (MeOH) by methanotrophic bacteria is an attractive and sustainable approach to producing MeOH. The model strain Methylosinus trichosporium OB3b has been reported to be an efficient hydroxylating biocatalyst. Previous works have shown that regardless of the bioreactor design or operation mode, MeOH concentration reaches a threshold after a few hours, but there are no investigations into the reasons behind this phenomenon. The present work entails monitoring both MeOH and formate concentrations during CH4 hydroxylation, where neither a gaseous substrate nor nutrient shortage was evidenced. Under the assayed reaction conditions, bacterial stress was shown to occur, but methanol was not responsible for this. Formate addition was necessary to start MeOH production. Nuclear magnetic resonance analyses with 13C-formate proved that the formate was instrumental in regenerating NADH; formate was exhausted during the reaction, but increased quantities of formate were unable to prevent MeOH production stop. The formate mass balance showed that the formate-to-methanol yield was around 50%, suggesting a cell regulation phenomenon. Hence, this study presents the possible physiological causes that need to be investigated further. Finally, to the best of our knowledge, this study shows that the reaction can be achieved in the native bacterial culture (i.e., culture medium containing added methanol dehydrogenase inhibitors) by avoiding the centrifugation steps while limiting the hands-on time and water consumption.